A provider's guide to primary myelofibrosis: pathophysiology, diagnosis, and management. (January 2021) - Garmezy, Benjamin; Schaefer, Jordan K.; Mercer, Jessica; Talpaz, Moshe
Abstract: Although understanding of the pathogenesis and molecular biology of primary myelofibrosis continues to improve, treatment options are limited, and several biological features remain unexplained. With an appropriate clinical history, exam, laboratory evaluation, and bone marrow biopsy, the diagnosis can often be established. Recent studies have better characterized prognostic factors and driver mutations in myelofibrosis, facilitated by use of next-generation sequencing. These advances have facilitated development of a management strategy that is based on both risk factors and clinical phenotype. For low-risk patients, treatment will depend on symptom severity. For patients with higher-risk disease, several treatments are available including JAK inhibitors, allogeneic hematopoietic stem cell transplant, and clinical trials using novel molecularly targeted therapies and rational drug combinations. In this review, we outline what is known about the disease pathogenesis, discuss an approach to reaching the diagnosis, review the prognosis of myelofibrosis, and detail current therapeutic strategies.